Curriculum Renewal for Evidence-based Practice : Implementing a Blended Learning Approach in Medicine. - Ilic, Dragan (Office for Learning and Teaching, 2014)
Evidence Based Practice (EBP) in medicine has evolved over the two last decades and now underpins medical practice. In recognition of its importance EBP has been incorporated in curricula as a core subject across many medical schools, usually taught didactically. Given the mantra of EBP states that all medical decisions should be informed by the best evidence, it is ironic that there is currently a dearth of evidence in this field with respect to its teaching and assessment. This is the final report from a randomised controlled trial (RCT) that examined the effectiveness of utilising a blended learning approach, compared to a didactic approach, to teaching EBP. This project also developed, validated, implemented and evaluated a novel tool that provides teacher, users and learners of EBP with an instrument that assesses competency in all aspects of EBP.